Porous calcium polyphosphate bone substitutes: Additive manufacturing versus conventional gravity sinter processing—Effect on structure and mechanical properties. Issue 2 (30th August 2013) - Hu, Youxin; Shanjani, Yaser; Toyserkani, Ehsan; Grynpas, Marc; Wang, Rizhi; Pilliar, Robert
Abstract Porous calcium polyphosphate (CPP) structures proposed as bone‐substitute implants and made by sintering CPP powders to form bending test samples of approximately 35 vol % porosity were machined from preformed blocks made either by additive manufacturing (AM) or conventional gravity sintering (CS) methods and the structure and mechanical characteristics of samples so made were compared. AM‐made samples displayed higher bending strengths (≈1.2–1.4 times greater than CS‐made samples), whereas elastic constant (i.e., effective elastic modulus of the porous structures) that is determined by material elastic modulus and structural geometry of the samples was ≈1.9–2.3 times greater for AM‐made samples. X‐ray diffraction analysis showed that samples made by either method displayed the same crystal structure forming β‐CPP after sinter annealing. The material elastic modulus, E, determined using nanoindentation tests also showed the same value for both sample types (i.e., E ≈ 64 GPa). Examination of the porous structures indicated that significantly larger sinter necks resulted in the AM‐made samples which presumably resulted in the higher mechanical properties. The development of mechanical properties was attributed to the different sinter anneal procedures required to make 35 vol % porous samples by the two methods. A primary objective of the present study, in addition to reporting on bending strength and sample stiffness (elastic constant) characteristics, was to determine why the two processes resulted in the observed mechanical property differences for samples of equivalent volume percentage of porosity. An understanding of the fundamental reason(s) for the observed effect is considered important for developing improved processes for preparation of porous CPP implants as bone substitutes for use in high load‐bearing skeletal sites. © 2013 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater, 102B: 274–283, 2014.